The Contributions of Professor M. V. Vinokurov to increasing technical speed of trains and improving the running qualities of railway carriage - N. V. Ustiak (History of science and technology, 2018)
The article is devoted to the contribution of Professor M. V. Vinokurov to solving the problem of increasing technical speed of trains and improving the running qualities of railway carriage. The analyze of experimental studies of M. V. Vinokurov showed a close connection between the well-being of passengers with smoothness of motion, the magnitude of the amplitudes and the frequency of the carriage vibrations. Particular attention was paid to the brake application of the rolling stock of trains.